2009
DOI: 10.1262/jrd.20239
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Anxiety with Relation to the Volume of the Locus Ceruleus in Progranulin-Deficient Mice

Abstract: Abstract. The mammalian brain exhibits sex differences with respect to structure and function. In our previous report, we found that progranulin (PGRN)-deficient (pgrn -/-) mice displayed an alteration in male-type behaviors, including reduced frequency of ejaculation and elevated levels of aggression and anxiety. The aim of the present study was to elucidate the role of PGRN in sex differences in anxiety. In the elevated plus maze, wild-type (pgrn +/+ ) female mice spent more time in the closed arms than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
2
10
1
Order By: Relevance
“…male and female rodents show different levels and patterns of food consumption [8], activity [9] and anxiety-related behaviours [10]. Whilst there is fairly consistent data regarding the direction of effects for the first two measures (whereby males consume more food and achieve higher bodyweights [11,12], and females are more active [13,14]), the data regarding the direction of anxiety-related behaviours is more uncertain [15,16]. This uncertainty could reflect inter-study heterogeneity related to the strain and species used, differences in experimental protocols, or failure to account for stage of female oestrus [17].…”
Section: Introductionmentioning
confidence: 99%
“…male and female rodents show different levels and patterns of food consumption [8], activity [9] and anxiety-related behaviours [10]. Whilst there is fairly consistent data regarding the direction of effects for the first two measures (whereby males consume more food and achieve higher bodyweights [11,12], and females are more active [13,14]), the data regarding the direction of anxiety-related behaviours is more uncertain [15,16]. This uncertainty could reflect inter-study heterogeneity related to the strain and species used, differences in experimental protocols, or failure to account for stage of female oestrus [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the open-field test, wt females generally show higher levels of anxiety than males and Grn loss raises the anxiety level of males significantly to similar levels of females [75]. A follow up-study on the same mice linked increased anxiety in Grn −/− males to an increase in the volume and number of cells in the locus ceruleus [185], a nucleus involved in physiological responses to stress and anxiety. Furthermore, Grn −/− males exhibited enhanced aggressiveness towards females and increased frequency of biting attacks in the resident-intruder test, which was ascribed to alterations in the brain serotonergic system of Grn −/− mice [75].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was suggested that the volumetric difference in the locus ceruleus of progranulin-deficient mice compared with controls was a possible cause of sexually dimorphic anxiety. 20 Given that progranulin deficiency in humans leads to FTLD-U, it was surprising that C-terminal cleavage products of the TDP-43 protein that are characteristic for human FTLD-U were not observed in these progranulin-deficient mice. 21 The objective of the current study was to characterize an aged series (1,7,12, and 23 months) of GRN-deficient ( Ϫ/ϩ and Ϫ/Ϫ ) mice to determine the neuropathological consequences of having partial or complete loss of PGRN function throughout life as a means to understand the biological role of PGRN in the CNS.…”
mentioning
confidence: 99%